PENGARUH PENERAPAN IFRS, AUDIT EFFORT, DAN KOMPLEKSITAS OPERASI PERUSAHAAN TERHADAP AUDIT DELAY - Santi Wijayanti; Effriyanti Effriyanti (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2019)
This study aims to test and prove empirically the influence of IFRS implementation, audit effort and complexity of company operations. This research was conducted at a real estate company listed on Indonesia Stock Exchange (BEI) in 2009-2017. The sample in this research by purposive sampling method. Research type is quantitative with quantitative descriptive method, obtained 9 companies that used as research sample with observation for 9 (nine) year, so total observation is 81 financial report which have been audited. The analysis method used is descriptive statistics, data quality test and hypothesis test with significance level of 5%. The results of this study indicate that the application of IFRS has no significant effect on audit delay, while audit effort has no effect on audit delay and the company's operating complexity has no significant effect on audit delay.